Indonesians’ readiness in facing long-term COVID-19 pandemic - Rendi Editya Darmawan; Yuyun Setyorini; Yopi Harwinanda Ardesa (Jurnal Ners, 2022)
Introduction: Long-term COVID-19 pandemic which has existed in Indonesia since 2020 not only poses a risk to public health but also to their social conditions. Indonesia, as a country with strong social fabric within its people, has a high sense of social responsibilities in facing the pandemic. The aim of this study is to describe Indonesians’ readiness in facing long-term COVID-19 pandemic. Methods: This descriptive study used a cross-sectional design with a sample of 305 residents of five cities in Indonesia. They were chosen not randomized by distributing a survey invitation via WhatsApp group with the background of the general public, and health cadres. We waited until the response received reached the targeted number of respondents. The data were collected using Google Forms, and were analyzed by using a descriptive method (percentage, P-value, and odds ratio) by SPSS statistical software version 25. Results: The readiness in facing the pandemic fell into two categories: the high readiness level (77.1%) and the low readiness level (22.9%). Gender and age do not affect the level of readiness, while the level of education and employment status influenced the level of readiness. Conclusions: The majority of Indonesians have high readiness level. Public participation can decrease COVID-19 transmission rate.